Alertness, self-efficacy, and intention: Mediating effects encouraging students entrepreneurship behavior - Andriyastuti Suratman; Ratna Roostika (Journal of Education and Learning (EduLearn), 2022)
This study examined the interaction of alertness, self-efficacy, and intention in entrepreneurial behavior. This research departed from the efforts of educational institutions to produce graduates with entrepreneurial profiles. Data was collected through questionnaires distributed to 530 respondents who had taken sharia entrepreneurship classes at a university in Indonesia. The results showed that education positively affected students' alerts and self-efficacy. Alertness and subsequent self-efficacy also positively impact entrepreneurial intention and behavior. Next, the entrepreneurial intention has a positive effect on entrepreneurial behavior. Contradictory findings show entrepreneurship education does not significantly impact entrepreneurial intention, self-efficacy, and behavior. The indirect effect found that the mediating role of alertness, self-efficacy, and purpose could fully bridge the relationship between education and entrepreneurial behavior. The results implied the importance of alertness, self-efficacy, and intention to promote entrepreneurial behavior in educational institutions. The study results highlighted an important message for universities and schools to put more effort into students' self-efficacy, vigilance, and personal intention to maximize learning activities on campus. The action can support the efforts of educational institutions through the entrepreneurship curriculum to increase the profile of alums as entrepreneurs.